Development of Flavor Variants and Packaging in the Fish Processing Community in Perancak Village, Jembrana District, Jembrana Regency, Bali - Ni Made Ayu Suardani Singapurwa; I Putu Candra; , I Nyoman Rudianta; Ni Komang Armaeni (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2023)
Pedetan